The Operational Risk Management in Banking – Evolution of Concepts and Principles, Basel II Challenges - Mirela-Anca SCHWARTZ-GÂRLIŞTE (Revista de Management Comparat International)
The operational risks in the bankinkg sector are undeniable realities of contemporary specific environment and their correct treatment is now both a necessity and a prerequisite for effective overall management process. Operational risk management brings a double challenge for banks. On the one hand the need to align with regulations in order to meet the requirements of the system’s regulators, on the other hand turning these requirements into a business opportunity. This paper is meant to provide an overlook on the operational risk management specific to the banking sector. The study briefly defines operational risk in banking and reviews the evolution of the good practices principles regarding operational risk management in banking. In the last part the paper paper deals with the approaches used for establishing the regulatory capital for operational risk as they were set by the Basel Committee for Banking Supervision: basic indicator approach, standardized approach and advanced measurement approach.